Effect of nitrogen and extraction method on algae lipid yield - Shen, Ying; Pei, Zhijian; Yuan, Wenqiao; Mao, Enrong (International Journal of Agricultural and Biological Engineering, 2009)
Effects of nitrogen source and concentration as well as lipid extraction method on the lipid yield of autotrophic Scenedesmus dimorphus and heterotrophic Chlorella protothecoides were studied. Three concentration levels of nitrate, urea and glycine/yeast extract as the nitrogen source were investigated. The highest lipid yield of S. dimorphus in the 17-d autotrophic culture was 0.40 g/L from the 1.8 g/L urea medium, and the maximum lipid yield of C. protothecoides in the nine-day heterotrophic culture was 5.89 g/L from the 2.4 g/L nitrate medium. Four different cell disruption methods— bead-beater, French press, sonication and wet milling— were studied for their effectiveness in solvent extraction of algal lipids from S. dimorphus and C. protothecoides. Wet milling followed by hexane extraction was most effective for S. dimorphus lipid extraction, whereas bead-beater disruption followed by hexane extraction was best for C. protothecoides. Key words: algae, nitrogen source, lipid content, lipid extraction, Scenedesmus dimorphus, Chlorella protothecoides DOI: 10.3965/j.issn.1934-6344.2009.01.051-057 Citation: Ying Shen, Zhijian Pei, Wenqiao Yuan, Enrong Mao. Effect of nitrogen and extraction method on algae lipid yield. Int J Agric & Biol Eng, 2009; 2(1): 51